Late Holocene high resolution multi-proxy climate and environmental records from Lake Van, eastern Turkey - Barlas Şimşek, F.; Çağatay, M.N. (Elsevier BV, 2018)
Abstract We present the multi-proxy records of centennial scale climate and environmental changes over the last 3.5 ka from a varved sediment core in Lake Van, eastern Turkey. The multi-proxy analyses include ostracod counts, μ-XRF elemental, total organic (TOC) and inorganic carbon, C-N elemental and stable isotopes. For the age model of the core, we use radionuclide (210Pb and 137Cs) analysis and varve counting. Large differences between Accelerator Mass Spectrometry (AMS) radiocarbon dates from TOC and varve ages indicate reservoir ages of 1.2–3.8 ka calBP. Average sedimentation rate for the last 170 years (top 75 mm of the core) ranges between 0.42 and 0.54 mm/yr according to 210Pb dating. Multi-proxy parameters show that Lake Van experienced more arid conditions during the 3.5–1.6 Ka calBP than those during the last 1.6 ka BP. 16 periods of alternating cold/dry and warm/wet intervals with 100–350 years duration are observed over the last 3.5 ka. The Lake Van climate records are conformable with the Lake Nar and the Sofular speleothem records as well as the European historical climate periods including Roman Warm Period (RWP), Dark Age Cold Period (DACP), Medieval Warm Period (MWP) and Little Ice Age (LIA), indicating teleconnections with the North Atlantic system. Human influence is reflected by high detrital influx in the last 700 years.